Cell Creeping and Controlled Migration by Magnetic Carbon Nanotubes - Ciofani G; Pensabene V; Raffa V; Vittorio O; Cuschieri A (Nanoscale Research Letters, 2009)
Abstract Carbon nanotubes (CNTs) are tubular nanostructures that exhibit magnetic properties due to the metal catalyst impurities entrapped at their extremities during fabrication. When mammalian cells are cultured in a CNT-containing medium, the nanotubes interact with the cells, as a result of which, on exposure to a magnetic field, they are able to move cells towards the magnetic source. In the present paper, we report on a model that describes the dynamics of this mammalian cell movement in a magnetic field consequent on CNT attachment. The model is based on Bell’s theory of unbinding dynamics of receptor-ligand bonds modified and validated by experimental data of the movement dynamics of mammalian cells cultured with nanotubes and exposed to a magnetic field, generated by a permanent magnet, in the vicinity of the cell culture wells. We demonstrate that when the applied magnetic force is below a critical value (about F c ≈ 10−11 N), the cell ‘creeps’ very slowly on the culture dish at a very low velocity (10–20 nm/s) but becomes detached from the substrate when this critical magnetic force is exceeded and then move towards the magnetic source.